The Pengaruh Latihan Sport Drajat Berbasis Rangkaian Bermain terhadap Keterampilan Teknik Dasar Petarung Tarung Derajat - Desi Purnama Sari; Alnedral Alnedral; Sayuti Syahara (Jurnal Sporta Saintika, 2025)
This study aimed to examine the effect of a play-based sequential training method on the fundamental technical skills of Tarung Derajat fighters. A quasi-experimental design with a pretest–posttest approach was employed. The research population consisted of 263 male Tarung Derajat athletes at Kurata III (green belt) level in West Sumatra. A purposive sampling technique was used to select 40 athletes as research participants. The instrument used is a validated and reliable Fighter Basic Skills Test with a reliability value of 0.96 and validity ranging from 0.71–0.85. Data were analyzed using a t-test to determine differences in technical skill performance before and after the training intervention. The results revealed that the calculated t value (15.53) exceeded the critical t value (2.093) at a 0.05 significance level, indicating a significant effect of the intervention. Furthermore, the mean score of fundamental technical skills increased from 54.70 in the pretest to 56.47 in the posttest. These findings demonstrate that play-based sequential training significantly improves fundamental technical skills in Tarung Derajat fighters. This training approach is considered effective as it provides dynamic, contextual, and game-like practice conditions that closely resemble real combat situations.